Transitivity Processes in Quantitative Versus Qualitative Applied Linguistics Research Articles' Discussions - Marzieh Bagherkazemi; Zahra Dehini; Maryam Jalali Moghaddam; Bita Ghalandar-Zehi (Research in English Language Pedagogy, 2023)
Transitivity and its associated clausal semantic processes are assumed to bear textual representations of reality and encode authors' conceptions of the world in linguistic terms. Given this and the differential epistemologies featuring quantitative and qualitative research, the transitivity analysis of their associated academic reports gains salience. This study involved the comparative transitivity analysis of the discussion sections of 40 quantitative and qualitative applied linguistics research articles. Relative distributions of the six transitivity processes in systemic functional linguistics (relational, material, verbal, mental, existential, and behavioral) were investigated through a series of Chi-Square tests. Moreover, the most frequent processes in quantitative and qualitative discussions were in terms of their semantic associations. The results showed that mental, relational, and behavioral processes were the most frequent in both quantitative and qualitative discussions. In addition, qualitative research articles' discussions housed more mental and material processes, while quantitative research articles' discussions involved a significantly higher number of relational, verbal, and behavioral processes. However, frequent processes were semantically similar in the two corpora. The results are discussed regarding the ideological and generic associations of quantitative and qualitative research. The findings have implications for academic writing instruction and shed light on linguistically encoded reality in quantitative and qualitative research articles.